Extent of irrationality of the consumer: Combining the Critical Cost Eciency and Houtman Maks Indices - Matej Opatrny (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We combine the Critical Cost Efficiency Index and the Houtman Maks Index to evaluate the consistency of subjects in a set of choice data from budgets. We show that by simply allowing subjects for one significant mistake (by removing the worst observation), the mean Critical Cost Efficiency Index in a set of choices from an online experiment with the general population increases by 6 percentage points. Furthermore, we find that by excluding the worst observation per subject, the fraction of subjects wasting 5% or less of their budget increases from 45% to 64%. The highest improvement in terms of efficiency can be seen among retired and 65+ aged subjects which indicates that their low level of effciency is largely due to a single mistake.
Keywords: D12; D14; D81; D83; D91; G11; 330; Critical Cost Efficiency Index; Houtman Maks Index; Socio-economic groups; observation